PAI Teacher's Personality Competencies In Strengthening Character - Shela Fahra Dilla; Asnil Aidah Ritonga (At-Tarbiyat, 2023)
This study aims to examine the discipline of Islamic Religious Education (PAI) teachers at SMP Negeri 28 Medan and find out the extent to which the discipline of Islamic Religious Education (PAI) teachers improves student character. The method used is a qualitative descriptive technique, and the type of research is field research. As the main data source, interviews with Islamic Religious Education teachers were used to collect information, followed by observations on PAI teachers' disciplinary practices and student character that could be improved. Data analysis techniques include data reduction, data presentation, and conclusion drawing or validation. The results showed that PAI teachers are quite disciplined, but not all student character development can be improved. By obeying school rules by arriving on time, student discipline can be improved. PAI instructors who carry out their main duties can increase student accountability. Consequently, when a teacher is strict with students, the value of discipline and responsibility of students will increase. This research contributes by providing input to schools on how to establish cooperation between teachers and parents so that character education in children is maximally strengthened.